PERLINDUNGAN PENGUNGSI DALAM PERSPEKTIF HUKUM INTERNASIONAL DAN HUKUM ISLAM (Studi Terhadap Kasus Manusia Perahu Rohingya) - Yuliantiningsih, Aryuni (Jurnal Dinamika Hukum, 2013)
The problem of refugees is a difficult problem that againts up by international community. Commonly, the reason of refugee because of  human rights violation in their State. In the end of 2011, based on report of United Nations, there are 47,5 million refugees from moslem majority, the one of them is called ‘The Boat People’ Rohingya. Islamic law had  interferenced regulation in  international law about protection for refugee . The refugees rights for protection by the host State regulated in Convention relating Status of Refugees 1951 and the protocol relating the Status of Refugee 1967. Islamic law regulated in QS Al Hasyr: 9. The principle of Non Refoulment is a principle that recognized under international law and Islamic law. Non refoulment is a concept in which state shall not return (refoule) a refugee or asylum seeker in any manner. This principle is become international customary law so every State must be implementing it.Key words : The protection of refugees, international law, Islamic law